Integrating participatory community mobilization process to improve dengue prevention, an eco bio social sacling up of local sucess in Machala, Ecuador. - Beltrán Ayala, Efraín (Netherlands, 2015)
Dengue is a major public health problem in Ecuador, with a diverse array of contributing factors and a lack of intersectoral organization within governance systems exacerbating it. Ecuador has identified all four dengue serotypes within its borders and the vector, Aedes aegypti is distributed throughout the tropical, sub tropical regions of the country as well as all of its islands. Moreover, there has been poor integration of approaches todengue prevention, especially with regard to primary education, social mobilization, poverty and deficie ncy of basic public services as determinants fordenguetransmission. Dengue control programs in Ecuador, as with many countries in the Americas, rely on govern ment application of temephos larvicide, deltamethrine adulticide andBacillus thuringiensis israelensis (bti) -based biolarvicide
Keywords: TRANSACTIONS OF THE ROYAL SOCIETY OF TROPICAL MEDICINE AND HYGIENE; PREVENCION DE DENGUE; ECOSISTEMA; ECUADOR